Modeling and in-situ evaluation of thermal gradients during sintering of large ceramic balls. Issue 9 (15th June 2017) - Gremillard, L.; Biotteau-Deheuvels, K.; Clement, P.; Perron, M.; Duvauchelle, P.; Meille, S.; Chevalier, J.
Abstract: During the sintering process of ceramic pieces, temperature gradients may arise inside the piece if the thermal cycle is too fast with regards to the size of the ceramic body. Too large temperature gradients may lead to density gradients, thus to strain gradients which may result in defects or in the fracture of the pieces. This article presents both an experimental setup and the first steps towards a numerical method to evaluate these thermal gradients and their evolutions during sintering, in the case of large zirconia, alumina and zirconia-toughened alumina balls. Finally it discusses the advantages of Rate Controlled Sintering thermal cycles in terms of diminishing the temperature gradients during densification.